A method for constructing a high-performance simple perovskite solar cell
Patent Information
- Application Number
- CN202311337115.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-10-17
AI Technical Summary
但已有的界面优化方法并不能有效提高界面载流子传输效率,界面材料也存在不易制备、稳定性较差、价格高昂等诸多问题,制约了简式PSCs的发展
[0017]本发明的有益效果在于:由于界面能级不匹配、薄膜缺陷多、界面接触差等问题,制备高效稳定的无电子(或空穴)传输层的简式钙钛矿太阳能电池充满挑战。而已有界面修饰材料存在成本高、不易获取、稳定性差等问题,也阻碍了简式PSCs的规模化和市场化。同时,大部分界面材料(比如极性有机小分子)通过构建界面内建电场起到传递界面电子的作用。因此从器件结构出发,这些电池并不属于简式钙钛矿太阳能电池。本发明以廉价易得、高稳定性的碱金属卤化物直接取代传统电子传输材料(如SnO2),该界面层并不能传递界面电子,而是发挥即优化基底表面能级结构又改善钙钛矿薄膜致密均一性的双重作用,从而构建真正意义上的无电子传输层的简式钙钛矿太阳能电池。另外,碱金属卤化物修饰层的制备工艺更加简单高效、低能耗、更易大面积成膜,有助于规模化应用。更重要的是,本发明系统分析了碱金属阳离子(Li+、Na+、K+)解离能和卤素阴离子(F-、Cl-、Br-、I-)电负性对钙钛矿薄膜和器件性能的影响,深入探索了碱金属卤化物的作用机制,为同类型界面材料的选择原则提供指导,为高性能简式钙钛矿太阳能电池的构建奠定基础。通过碱金属卤化物修饰后的简式PSCs表现出非常优异的光电转换效率和稳定性。其中KF基简式器件效率达到23.04%,这也是目前报道的刚性无电子传输层PSCs的最高效率,无封装器件在最大功率点(Pmax)处1500h后效率仍保持90%以上。
Smart Images

Figure CN117396008B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photovoltaic technology, and in particular relates to a method for constructing a high-performance simplified perovskite solar cell with high efficiency and stability achieved by using an alkali metal halide modification layer. Background Technology
[0002] Solar energy is a very important clean and renewable energy source with many advantages, including abundant energy reserves, wide coverage, and no geographical limitations. Photovoltaic technology can directly convert solar energy into electricity, greatly reducing human dependence on non-renewable fossil fuels and effectively reducing greenhouse gas emissions, which is of positive significance for mitigating climate change and protecting the environment.
[0003] In recent years, perovskite solar cells (PSCs) using organic-inorganic lead halide perovskite as the light-absorbing layer have developed rapidly, achieving certified efficiencies as high as 26.1%, comparable to traditional crystalline silicon solar cells. This makes PSCs one of the most promising next-generation photovoltaic technologies. High-performance perovskite solar cells are mainly based on a "sandwich" structure of multifunctional layers: conductive substrate / electron or hole transport layer / perovskite light-absorbing layer / hole or electron transport layer / counter electrode. Various modification layers are often introduced between the basic functional layers to improve interfacial carrier transport efficiency, making the PSC structure more complex, extending the production cycle, and increasing the manufacturing cost. Among them, tin dioxide (SnO2) produced in Japan is a commonly used electron transport material in high-performance PSCs. However, the high price, complex composition, and cumbersome synthesis process of SnO2 dispersions have led to a severe shortage of this product in the domestic market. Currently, there is no better electron transport material to replace imported SnO2, which greatly limits the development of perovskite photovoltaic technology. Therefore, it is particularly important to abandon the traditional SnO2 electron transport layer and construct a high-performance, simplified perovskite photovoltaic device without an electron transport layer.
[0004] The absence of an electron transport layer leads to severe interfacial nonradiative recombination, a major factor limiting the efficiency and stability of simplified perovskite photovoltaic (PSCs). Optimizing the interfacial structure and photophysical properties has become crucial for improving the performance of simplified devices. However, existing interfacial optimization methods cannot effectively improve interfacial carrier transport efficiency, and interfacial materials suffer from numerous problems such as difficulty in preparation, poor stability, and high cost, hindering the development of simplified PSCs. Therefore, developing novel, low-cost interfacial optimization materials and methods has become an important research topic in the field of simplified perovskite photovoltaics. Summary of the Invention
[0005] The purpose of this invention is to address the aforementioned problems in the prior art by providing a method for constructing a high-performance, simplified perovskite solar cell. This method abandons traditional electron transport materials and uses inexpensive and readily available alkali metal halides as a modification layer for the conductive substrate, thereby constructing a simplified perovskite solar cell with high efficiency and high stability without an electron transport layer.
[0006] To achieve the above objectives, the technical solution of this invention is as follows: An alkali metal halide modification layer AX is introduced at the interface between the conductive substrate and the perovskite buried substrate, simultaneously optimizing the surface energy level structure of the substrate and the nucleation and crystallization kinetics of the perovskite, thereby improving the interface carrier injection and transport efficiency, and thus obtaining a high-performance simplified perovskite solar cell. The specific steps are as follows:
[0007] 1) Treatment of conductive substrate: Cut the conductive substrate into standard size, and ultrasonically clean it in sequence with glass cleaning fluid, deionized water, acetone, ethanol and isopropanol. After drying, treat it with a UV-ozone cleaner and collect it for later use.
[0008] 2) Preparation of alkali metal halide modified layer: Prepare an aqueous solution of alkali metal halide with deionized water and spin-coat it onto a conductive substrate, and then anneal the conductive substrate modified with metal halide.
[0009] 3) Preparation of perovskite light-absorbing layer: Prepare perovskite precursor solution with a mixed solvent of DMF and DMSO, prepare perovskite light-absorbing layer by one-step spin coating in a glove box, and anneal the perovskite film.
[0010] 4) Preparation of hole transport layer: Prepare a chlorobenzene solution of Spiro-OMeTAD, add tBP and Li-TFSI acetonitrile solution, and then spin-coat the film in a glove box;
[0011] 5) Preparation of metal counter electrodes: High work function Au or Ag counter electrodes are prepared by vacuum thermal evaporation.
[0012] In step 1), the conductive substrate is fluorine-doped tin oxide (FTO) conductive glass; the ultrasonic cleaning time can be 10-20 min; the ultraviolet-ozone cleaning time can be 10-20 min.
[0013] In step 2), the alkali metal halide is selected from any one of LiF, NaF, KF, KCl, KBr, and KI; the concentration of the aqueous solution of the alkali metal halide can be 1–4 mg / mL; the spin coating speed can be 1000–3000 rpm, and the spin coating time can be 10–30 s; the annealing can be performed at 100–150 °C for 10–30 min.
[0014] In step 3), the perovskite material is FACsMAPb(I 0.92 Br0.08 )3; The volume ratio of DMF to DMSO in the solvent is 1:4; The perovskite light-absorbing layer is prepared by one-step spin coating, and the film is formed by spin coating in a glove box. The spin coating speed is 1000-4000 rpm and the spin coating time is 10-30s. Then, it is annealed at 100℃ for 20-50min. The antisolvent is ethyl acetate.
[0015] In step 4), the concentration of the chlorobenzene solution of Spiro-OMeTAD can be 60-80 mg / mL; the concentration of the acetonitrile solution of Li-TFSI is 520 mg / mL; and the thickness of Spiro-OMeTAD is 10-50 nm.
[0016] In step 5), the thickness of the electrode can be 30 to 120 nm.
[0017] The beneficial effects of this invention are as follows: Fabricating efficient and stable simplified perovskite solar cells without an electron (or hole) transport layer is challenging due to problems such as interface energy level mismatch, numerous thin film defects, and poor interface contact. Existing interface modification materials suffer from high cost, scarcity, and poor stability, hindering the large-scale production and marketization of simplified PSCs. Furthermore, most interface materials (such as polar organic small molecules) transfer interface electrons by constructing an internal electric field. Therefore, from a device structure perspective, these cells do not belong to simplified perovskite solar cells. This invention directly replaces traditional electron transport materials (such as SnO2) with inexpensive, readily available, and highly stable alkali metal halides. This interface layer does not transfer interface electrons but plays a dual role in optimizing the substrate surface energy level structure and improving the density and uniformity of the perovskite thin film, thus constructing a truly simplified perovskite solar cell without an electron transport layer. In addition, the preparation process of the alkali metal halide modification layer is simpler, more efficient, lower in energy consumption, and easier to form large-area films, which is conducive to large-scale applications. More importantly, this invention systematically analyzes the alkali metal cation (Li... + Na + K + Dissociation energy and halide anion (F) - Cl - ,Br - I - The influence of electronegativity on the performance of perovskite thin films and devices was investigated, and the mechanism of action of alkali metal halides was explored in depth. This provides guidance for the selection principles of similar interface materials and lays the foundation for the construction of high-performance simplified perovskite solar cells. The simplified PSCs modified with alkali metal halides exhibited excellent photoelectric conversion efficiency and stability. The KF-based simplified device achieved an efficiency of 23.04%, which is the highest efficiency reported to date for rigid PSCs without an electron transport layer. The unencapsulated device maintained an efficiency of over 90% after 1500 hours at the maximum power point (Pmax). Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the fabrication process for a simplified perovskite solar cell without an electron transport layer.
[0019] Figure 2 This is a schematic diagram of a simplified perovskite solar cell without an electron transport layer.
[0020] Figure 3 This is a schematic diagram showing the spread of water and perovskite precursor solution droplets on conductive substrates modified with different alkali metal halides.
[0021] Figure 4 The statistical distribution of contact angles of water and perovskite precursor solutions on different substrates is shown in the figure.
[0022] Figure 5 A schematic diagram comparing the band structure of FTO and FTO-KF (KF modified layer) surfaces.
[0023] Figure 6 The microstructures of perovskite films on FTO and FTO-KF substrates are shown in (A) upper surface, (B) buried surface and (C) cross section, as well as (D) UV-Vis absorption spectrum, (E) X-ray diffraction spectrum, (F, G) fluorescence intensity of buried surface and (H, I) photoluminescence spectrum of buried interface.
[0024] Figure 7 (A) Appearance of a simplified perovskite solar cell; (B) Current-voltage curves of the simplified device before and after KF treatment, showing forward and reverse voltage scans.
[0025] Figure 8 Statistical distribution of efficiency of simplified devices after treatment with different alkali metal halides.
[0026] Figure 9 (A) Schematic diagram of the stability of the simplified device under long-term illumination at the maximum power point (MPP) before and after KF treatment; (B) Comparison of the device's appearance before and after the stability test. Test environment: N2, temperature 25-30℃. Detailed Implementation
[0027] To make the technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be further described below with reference to the accompanying drawings. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0028] Example 1:
[0029] like Figure 1The specific steps for fabricating a simplified perovskite solar cell based on a KF-modified layer in this embodiment are as follows:
[0030] (1) Treatment of conductive substrate: In this embodiment, a sheet resistance of 12Ω / cm is used. 2 Using FTO conductive glass as a substrate, the FTO was first cut into 2x2cm pieces. 2 To achieve the standard dimensions, laser etching was performed. The glass was then sequentially ultrasonicated for 15 minutes each with glass cleaning fluid, deionized water, acetone, ethanol, and isopropanol, and dried with compressed air. Finally, the glass was cleaned using a UV-ozone cleaner for 20 minutes and collected for later use.
[0031] (2) Preparation of alkali metal halide modified layer: Weigh 8 mg of KF solid powder, pour it into deionized water, stir for 15 min, and prepare an aqueous solution with a concentration of 4 mg / mL. Prepare the alkali metal halide modified layer in an atmospheric environment. Take 80 μL of the above solution, drop it onto FTO glass, and spin-coat it to form a film. The spin-coating speed is 3000 rpm, and the spin-coating time is 30 s. Heat the FTO-KF glass to 150℃, hold for 30 min, and let it cool naturally for later use.
[0032] (3)FA 0.9 Cs 0.07 MA 0.03 Pb(I 0.92 Br 0.08 Preparation of the light-absorbing layer: Weigh MAI (6.4 mg), FABr (13.5 mg), CsI (24.6 mg), MACl (31.9 mg), PbBr2 (39.6 mg), FAI (190.4 mg), and PbI2 (591.2 mg) and dissolve them in 1 mL of DMF / DMSO (v:v = 1:4) and stir overnight. Then, filter the homogenized perovskite solution through a PTFE filter (0.45 μm). Prepare the perovskite film in a glove box by taking 40 μL of the above solution and dropping it onto the substrate treated in step (2), then spin-coating to form a film. Specifically, a one-step spin-coating process was performed at 1000 rpm for 10 s and 4000 rpm for 30 s. In the last 10 s of the spin-coating process, 260 μL of ethyl acetate was rapidly dropped into the film as an antisolvent, followed by annealing at 100 °C for 40 min in a 30–35% humidity environment.
[0033] (4) Preparation of Spiro-OMeTAD hole transport layer: 144.6 mg of Spiro-OMeTAD solid powder was weighed and dissolved in 2 mL of chlorobenzene. An additional 57.6 μL of tBP and 35 μL of Li-TFSI acetonitrile solution were added, resulting in a concentration of 520 mg / mL. The film was then spin-coated in a glove box at a spin rate of 3000 rpm for 30 s, achieving a film thickness of 20–30 nm.
[0034] (5) Preparation of the Ag metal electrode: The FTO glass obtained in step (4) was placed in a metal mold, and a silver metal electrode was prepared by vacuum thermal evaporation. The evaporation rate was [missing information]. Vacuum degree is 10 -5 Pa, with a deposition thickness of 60–90 nm, yields an effective area of 0.09 cm². 2 A simplified perovskite solar cell.
[0035] Example 2:
[0036] like Figure 1 The specific steps for fabricating a simplified perovskite solar cell based on a LiF-modified layer in this embodiment are as follows:
[0037] (1) Treatment of conductive substrate: In this embodiment, a sheet resistance of 12Ω / cm is used. 2 Using FTO conductive glass as a substrate, the FTO was first cut into 2x2cm pieces. 2 To achieve the standard dimensions, laser etching was performed. The glass was then sequentially ultrasonicated for 15 minutes each with glass cleaning fluid, deionized water, acetone, ethanol, and isopropanol, and dried with compressed air. Finally, the glass was cleaned using a UV-ozone cleaner for 20 minutes and collected for later use.
[0038] (2) Preparation of alkali metal halide modified layer: Weigh 3.57 mg of LiF solid powder, pour it into deionized water, stir for 20 min, and prepare an aqueous solution with a concentration of 4 mg / mL. Prepare the alkali metal halide modified layer in an atmospheric environment. Take 80 μL of the above solution, drop it onto FTO glass, and spin-coat it to form a film. The spin-coating speed is 3000 rpm, and the spin-coating time is 30 s. Heat the FTO-LiF glass to 150 °C, hold for 30 min, and allow it to cool naturally for later use.
[0039] (3)FA 0.9 Cs 0.07 MA 0.03 Pb(I 0.92 Br 0.08Preparation of the light-absorbing layer: Weigh MAI (6.4 mg), FABr (13.5 mg), CsI (24.6 mg), MACl (31.9 mg), PbBr2 (39.6 mg), FAI (190.4 mg), and PbI2 (591.2 mg) and dissolve them in 1 mL of DMF / DMSO (v:v = 1:4) and stir overnight. Then, filter the homogenized perovskite solution through a PTFE filter (0.45 μm). Prepare the perovskite film in a glove box by taking 40 μL of the above solution and dropping it onto the substrate treated in step (2), then spin-coating to form a film. Specifically, a one-step spin-coating process was performed at 1000 rpm for 10 s and 4000 rpm for 30 s. In the last 10 s of the spin-coating process, 260 μL of ethyl acetate was rapidly dropped into the film as an antisolvent, followed by annealing at 100 °C for 40 min in a 30–35% humidity environment.
[0040] (4) Preparation of Spiro-OMeTAD hole transport layer: 144.6 mg of Spiro-OMeTAD solid powder was weighed and dissolved in 2 mL of chlorobenzene. An additional 57.6 μL of tBP and 35 μL of Li-TFSI acetonitrile solution was added, resulting in a concentration of 520 mg / mL. The film was then spin-coated in a glove box at a speed of 3000 rpm for 30 s, achieving a film thickness of 20–30 nm.
[0041] (5) Preparation of the Ag metal electrode: The FTO glass obtained in step (4) was placed in a metal mold, and a silver metal electrode was prepared by vacuum thermal evaporation. The evaporation rate was [missing information]. Vacuum degree is 10 -5 Pa, with a deposition thickness of 60–90 nm, yields an effective area of 0.09 cm². 2 A simplified perovskite solar cell.
[0042] Example 3:
[0043] like Figure 1 The specific steps for fabricating a simplified perovskite solar cell based on a NaF-modified layer in this embodiment are as follows:
[0044] (1) Treatment of conductive substrate: In this embodiment, a sheet resistance of 12Ω / cm is used. 2 Using FTO conductive glass as a substrate, the FTO was first cut into 2x2cm pieces. 2 To achieve the standard dimensions, laser etching was performed. The glass was then sequentially ultrasonicated for 15 minutes each with glass cleaning fluid, deionized water, acetone, ethanol, and isopropanol, and dried with compressed air. Finally, the glass was cleaned using a UV-ozone cleaner for 20 minutes and collected for later use.
[0045] (2) Preparation of alkali metal halide modified layer: Weigh 5.78 mg of NaF solid powder, pour it into deionized water, stir for 20 min, and prepare an aqueous solution with a concentration of 4 mg / mL. Prepare the alkali metal halide modified layer in an atmospheric environment. Take 80 μL of the above solution, drop it onto FTO glass, and spin-coat to form a film. The spin-coating speed is 3000 rpm, and the spin-coating time is 30 s. Heat the FTO-NaF glass to 150 °C, hold for 30 min, and allow it to cool naturally for later use.
[0046] (3)FA 0.9 Cs 0.07 MA 0.03 Pb(I 0.92 Br 0.08 Preparation of the light-absorbing layer: Weigh MAI (6.4 mg), FABr (13.5 mg), CsI (24.6 mg), MACl (31.9 mg), PbBr2 (39.6 mg), FAI (190.4 mg), and PbI2 (591.2 mg) and dissolve them in 1 mL of DMF / DMSO (v:v = 1:4) and stir overnight. Then, filter the homogenized perovskite solution through a PTFE filter (0.45 μm). Prepare the perovskite film in a glove box by taking 40 μL of the above solution and dropping it onto the substrate treated in step (2), then spin-coating to form a film. Specifically, a one-step spin-coating process was performed at 1000 rpm for 10 s and 4000 rpm for 30 s. In the last 10 s of the spin-coating process, 260 μL of ethyl acetate was rapidly dropped into the film as an antisolvent, followed by annealing at 100 °C for 40 min in a 30–35% humidity environment.
[0047] (4) Preparation of Spiro-OMeTAD hole transport layer: 144.6 mg of Spiro-OMeTAD solid powder was weighed and dissolved in 2 mL of chlorobenzene. An additional 57.6 μL of tBP and 35 μL of Li-TFSI acetonitrile solution was added, resulting in a concentration of 520 mg / mL. The film was then spin-coated in a glove box at a spin rate of 3000 rpm for 30 s, achieving a film thickness of 20–30 nm.
[0048] (5) Preparation of the Ag metal electrode: The FTO glass obtained in step (4) was placed in a metal mold, and a silver metal electrode was prepared by vacuum thermal evaporation. The evaporation rate was [missing information]. Vacuum degree is 10 -5 Pa, with a deposition thickness of 60–90 nm, yields an effective area of 0.09 cm². 2 A simplified perovskite solar cell.
[0049] Example 4:
[0050] like Figure 1The specific steps for fabricating a simplified perovskite solar cell based on a KCl-modified layer in this embodiment are as follows:
[0051] (1) Treatment of conductive substrate: In this embodiment, a sheet resistance of 12Ω / cm is used. 2 Using FTO conductive glass as a substrate, the FTO was first cut into 2x2cm pieces. 2 To achieve the standard dimensions, laser etching was performed. The glass was then sequentially ultrasonicated for 15 minutes each with glass cleaning fluid, deionized water, acetone, ethanol, and isopropanol, and dried with compressed air. Finally, the glass was cleaned using a UV-ozone cleaner for 20 minutes and collected for later use.
[0052] (2) Preparation of alkali metal halide modified layer: Weigh 10.26 mg of KCl solid powder, pour it into deionized water, stir for 20 min, and prepare an aqueous solution with a concentration of 4 mg / mL. Prepare the alkali metal halide modified layer in an atmospheric environment. Take 80 μL of the above solution, drop it onto FTO glass, and spin-coat it to form a film. The spin-coating speed is 3000 rpm, and the spin-coating time is 30 s. Heat the FTO-KCl glass to 150 °C, hold for 30 min, and let it cool naturally for later use.
[0053] (3)FA 0.9 Cs 0.07 MA 0.03 Pb(I 0.92 Br 0.08 Preparation of the light-absorbing layer: Weigh MAI (6.4 mg), FABr (13.5 mg), CsI (24.6 mg), MACl (31.9 mg), PbBr2 (39.6 mg), FAI (190.4 mg), and PbI2 (591.2 mg) and dissolve them in 1 mL of DMF / DMSO (v:v = 1:4) and stir overnight. Then, filter the homogenized perovskite solution through a PTFE filter (0.45 μm). Prepare the perovskite film in a glove box by taking 40 μL of the above solution and dropping it onto the substrate treated in step (2), then spin-coating to form a film. Specifically, a one-step spin-coating process was performed at 1000 rpm for 10 s and 4000 rpm for 30 s. In the last 10 s of the spin-coating process, 260 μL of ethyl acetate was rapidly dropped into the film as an antisolvent, followed by annealing at 100 °C for 40 min in a 30–35% humidity environment.
[0054] (4) Preparation of Spiro-OMeTAD hole transport layer: 144.6 mg of Spiro-OMeTAD solid powder was weighed and dissolved in 2 mL of chlorobenzene. An additional 57.6 μL of tBP and 35 μL of Li-TFSI acetonitrile solution was added, resulting in a concentration of 520 mg / mL. The film was then spin-coated in a glove box at a spin rate of 3000 rpm for 30 s, achieving a film thickness of 20–30 nm.
[0055] (5) Preparation of the Ag metal electrode: The FTO glass obtained in step (4) was placed in a metal mold, and a silver metal electrode was prepared by vacuum thermal evaporation. The evaporation rate was [missing information]. Vacuum degree is 10 -5 Pa, with a deposition thickness of 60–90 nm, yields an effective area of 0.09 cm². 2 A simplified perovskite solar cell.
[0056] Example 5:
[0057] like Figure 1 The specific steps for fabricating a simplified perovskite solar cell based on a KBr-modified layer in this embodiment are as follows:
[0058] (1) Treatment of conductive substrate: In this embodiment, a sheet resistance of 12Ω / cm is used. 2 Using FTO conductive glass as a substrate, the FTO was first cut into 2x2cm pieces. 2 To achieve the standard dimensions, laser etching was performed. The glass was then sequentially ultrasonicated for 15 minutes each with glass cleaning fluid, deionized water, acetone, ethanol, and isopropanol, and dried with compressed air. Finally, the glass was cleaned using a UV-ozone cleaner for 20 minutes and collected for later use.
[0059] (2) Preparation of alkali metal halide modified layer: Weigh 16.39 mg of KBr solid powder, pour it into deionized water, stir for 20 min, and prepare an aqueous solution with a concentration of 4 mg / mL. Prepare the alkali metal halide modified layer in an atmospheric environment. Take 80 μL of the above solution, drop it onto FTO glass, and spin-coat it to form a film. The spin-coating speed is 3000 rpm, and the spin-coating time is 30 s. Heat the FTO-KBr glass to 150 °C, hold for 30 min, and allow it to cool naturally for later use.
[0060] (3)FA 0.9 Cs 0.07 MA 0.03 Pb(I 0.92 Br 0.08Preparation of the light-absorbing layer: Weigh MAI (6.4 mg), FABr (13.5 mg), CsI (24.6 mg), MACl (31.9 mg), PbBr2 (39.6 mg), FAI (190.4 mg), and PbI2 (591.2 mg) and dissolve them in 1 mL of DMF / DMSO (v:v = 1:4) and stir overnight. Then, filter the homogenized perovskite solution through a PTFE filter (0.45 μm). Prepare the perovskite film in a glove box by taking 40 μL of the above solution and dropping it onto the substrate treated in step (2), then spin-coating to form a film. Specifically, a one-step spin-coating process was performed at 1000 rpm for 10 s and 4000 rpm for 30 s. In the last 10 s of the spin-coating process, 260 μL of ethyl acetate was rapidly dropped into the film as an antisolvent, followed by annealing at 100 °C for 40 min in a 30–35% humidity environment.
[0061] (4) Preparation of Spiro-OMeTAD hole transport layer: 144.6 mg of Spiro-OMeTAD solid powder was weighed and dissolved in 2 mL of chlorobenzene. An additional 57.6 μL of tBP and 35 μL of Li-TFSI acetonitrile solution was added, resulting in a concentration of 520 mg / mL. The film was then spin-coated in a glove box at a spin rate of 3000 rpm for 30 s, achieving a film thickness of 20–30 nm.
[0062] (5) Preparation of the Ag metal electrode: The FTO glass obtained in step (4) was placed in a metal mold, and a silver metal electrode was prepared by vacuum thermal evaporation. The evaporation rate was [missing information]. Vacuum degree is 10 -5 Pa, with a deposition thickness of 60–90 nm, yields an effective area of 0.09 cm². 2 A simplified perovskite solar cell.
[0063] Example 6:
[0064] like Figure 1 The specific steps for fabricating a simplified perovskite solar cell based on a KI-modified layer in this embodiment are as follows:
[0065] (1) Treatment of conductive substrate: In this embodiment, a sheet resistance of 12Ω / cm is used. 2 Using FTO conductive glass as a substrate, the FTO was first cut into 2x2cm pieces. 2 To achieve the standard dimensions, laser etching was performed. The glass was then sequentially ultrasonicated for 15 minutes each with glass cleaning fluid, deionized water, acetone, ethanol, and isopropanol, and dried with compressed air. Finally, the glass was cleaned using a UV-ozone cleaner for 20 minutes and collected for later use.
[0066] (2) Preparation of alkali metal halide modified layer: Weigh 22.86 mg of KI solid powder, pour it into deionized water, stir for 30 min, and prepare an aqueous solution with a concentration of 4 mg / mL. Prepare the alkali metal halide modified layer in an atmospheric environment. Take 80 μL of the above solution, drop it onto FTO glass, and spin-coat it to form a film. The spin-coating speed is 3000 rpm, and the spin-coating time is 30 s. Heat the FTO-KI glass to 150 °C, hold for 30 min, and allow it to cool naturally for later use.
[0067] (3)FA 0.9 Cs 0.07 MA 0.03 Pb(I 0.92 Br 0.08 Preparation of the light-absorbing layer: Weigh MAI (6.4 mg), FABr (13.5 mg), CsI (24.6 mg), MACl (31.9 mg), PbBr2 (39.6 mg), FAI (190.4 mg), and PbI2 (591.2 mg) and dissolve them in 1 mL of DMF / DMSO (v:v = 1:4) and stir overnight. Then, filter the homogenized perovskite solution through a PTFE filter (0.45 μm). Prepare the perovskite film in a glove box by taking 40 μL of the above solution and dropping it onto the substrate treated in step (2), then spin-coating to form a film. Specifically, a one-step spin-coating process was performed at 1000 rpm for 10 s and 4000 rpm for 30 s. In the last 10 s of the spin-coating process, 260 μL of ethyl acetate was rapidly dropped into the film as an antisolvent, followed by annealing at 100 °C for 40 min in a 30–35% humidity environment.
[0068] (4) Preparation of Spiro-OMeTAD hole transport layer: 144.6 mg of Spiro-OMeTAD solid powder was weighed and dissolved in 2 mL of chlorobenzene. An additional 57.6 μL of tBP and 35 μL of Li-TFSI acetonitrile solution was added, resulting in a concentration of 520 mg / mL. The film was then spin-coated in a glove box at a spin rate of 3000 rpm for 30 s, achieving a film thickness of 20–30 nm.
[0069] (5) Preparation of the Ag metal electrode: The FTO glass obtained in step (4) was placed in a metal mold, and a silver metal electrode was prepared by vacuum thermal evaporation. The evaporation rate was [missing information]. Vacuum degree is 10 -5 Pa, with a deposition thickness of 60–90 nm, yields an effective area of 0.09 cm². 2 A simplified perovskite solar cell.
[0070] This invention constructs a simplified device with a structure of "FTO-AX / perovskite / Spiro-OMeTAD / metal counter electrode", as shown in the figure. Figure 2 As shown, from bottom to top, the structure consists of an FTO conductive substrate, an alkali metal halide modification layer, a perovskite light-absorbing layer, and a hole transport layer. A metal counter electrode is disposed on the upper surface of the hole transport layer. Photovoltaic performance tests were conducted on the above simplified device, and the effects of different alkali metal halides on the substrate surface properties and device efficiency were compared and analyzed.
[0071] Alkali metal halides optimize the band structure of conductive substrates and the crystallization kinetics of perovskites, effectively suppressing nonradiative recombination losses of interfacial carriers and significantly improving the photoelectric conversion efficiency and stability of basic devices. However, different alkali metal halides exhibit significant differences in their ability to improve thin film properties and device efficiency. Specific experimental results are as follows: Figure 3 , Figure 4 and Figure 8 As shown, the simplified perovskite solar cell with KF as the modification layer exhibits the best photoelectric conversion efficiency (23.04%) and light stability (as shown). Figure 7 and Figure 9 This invention simplifies the structure of perovskite solar photovoltaic devices, eliminates reliance on traditional electron transport materials, shortens the battery fabrication process and production cycle, and greatly reduces device costs, which is conducive to the industrialization and large-scale production of perovskite solar cells.
[0072] The following tests analyze the effects of different alkali metal halides on the physicochemical properties of thin films and the photovoltaic performance of devices. The specific test results are as follows:
[0073] (1) Surface wettability and energy level structure of FTO: The contact angles of water and perovskite precursor solutions on the FTO-AX surface were tested, and the experimental results are as follows: Figure 3 and 4 As shown, different alkali metal halides have varying degrees of influence on the wettability of FTO surfaces. The FTO-KF surface exhibits the smallest contact angle and the best wettability, primarily because KF possesses the strongest electronegativity of a halide anion and the most suitable lattice dissociation energy. The surface energy level structure of the substrate before and after KF modification is shown in the figure. Figure 5 As shown, calculations revealed that the Fermi levels of FTO and FTO-KF are -4.36 eV and -3.90 eV, respectively. The increase in the Fermi level is mainly attributed to the formation of interfacial dipoles. The strong bonding between KF and FTO creates a intrinsic electric field at the substrate / perovskite interface, reducing the work function at the substrate surface and consequently increasing the open-circuit voltage of the device. Furthermore, the reduction in work function reverses the direction of band bending in the active layer (from top to bottom), promoting efficient extraction and transfer of interfacial charges. Simultaneously, the interfacial band bending also enhances hole blocking capability, effectively suppressing charge recombination dynamics.
[0074] (2) Photophysical properties of perovskite thin films: The quality of the perovskite thin film is a crucial factor determining the photovoltaic performance of the device. This invention uses scanning electron microscopy to test the microstructure of the upper and lower interfaces and the cross-section of the perovskite thin film. For example... Figure 6 As shown, the grain size on the upper and buried surfaces of the FT-KF-based perovskite is significantly increased, the grains are more densely and uniformly packed, and the physical contact between the perovskite and the upper and lower functional layers is also significantly improved. The increase in characteristic X-ray diffraction peak intensity, the improvement in ultraviolet-visible light absorption capacity, and the increase in fluorescence intensity on the buried surface further confirm the improved quality of the perovskite film, all of which are beneficial to the directional transport of interfacial charge carriers.
[0075] (3) Device efficiency and stability: Figure 7 Figure A shows the external structure of simplified PSCs; the devices modified with different alkali metal halides do not differ significantly in appearance. The current-voltage curves of the KF-based simplified devices are shown below. Figure 7 As shown in Figure B, compared with the control group (FTO-R / F), the efficiency of the KF-modified device is significantly improved, and the hysteresis effect is significantly reduced. The efficiency distribution of the simplified device after modification with different alkali metal halides is shown in Figure B. Figure 8 As shown. Among them, the KF-based device has the best champion efficiency, reaching 23.04%, which is also the highest efficiency reported to date for rigid electron transport layer-less PSCs.
[0076] Furthermore, this invention investigates the effect of the KF modification layer on the stability of unencapsulated simplified devices. For example... Figure 9 As shown in Figure A, under long-term illumination, the efficiency of the control group device decreased rapidly, with an initial efficiency decrease of 16.90% within 1148 hours, while the KF-based simplified device could still maintain an initial efficiency of 90.93% within 1540 hours. Figure 9 Figure B shows the changes in the device appearance before and after the stability test. After prolonged continuous illumination, the color of the perovskite layer in the KF-based simplified device did not change significantly, while the perovskite film in the control group showed obvious degradation (color changed from blue to red). This is because the KF modification layer optimizes the crystallization kinetics of perovskite growth, significantly reducing defects and pores at the upper and lower interfaces of the perovskite film, thereby effectively slowing down the degradation of the perovskite.
[0077] The above description is merely a preferred embodiment of the present invention. However, the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Anyone skilled in the art should understand that any equivalent substitutions or modifications made based on the technical solutions and improved concepts of the present invention are covered within the protection scope of the present invention.
Claims
1. A method for constructing a high-performance simplified perovskite solar cell, characterized in that... An alkali metal halide modification layer is introduced at the interface between a conductive substrate and a buried perovskite substrate to simultaneously optimize the surface energy level structure of the substrate and the nucleation and crystallization kinetics of the perovskite, thereby improving the interface carrier injection and transport efficiency and obtaining a high-performance simplified perovskite solar cell. The specific steps of the method are as follows: 1) Treatment of conductive substrate: Cut the conductive substrate into standard size, and ultrasonically clean it in sequence with glass cleaning fluid, deionized water, acetone, ethanol and isopropanol. After drying, treat it with a UV-ozone cleaner and collect it for later use. 2) Preparation of alkali metal halide modified layer: Prepare an aqueous solution of alkali metal halide with deionized water and spin-coat it onto a conductive substrate, and then anneal the conductive substrate modified with metal halide. 3) Preparation of perovskite light-absorbing layer: Prepare perovskite precursor solution with a mixed solvent of DMF and DMSO, prepare perovskite light-absorbing layer by one-step spin coating in a glove box, and anneal the perovskite film. 4) Preparation of hole transport layer: Prepare a chlorobenzene solution of Spiro-OMeTAD, add tBP and Li-TFSI acetonitrile solution, and then spin-coat the film in a glove box; 5) Preparation of metal counter electrodes: High work function Au or Ag counter electrodes are prepared by vacuum thermal evaporation.
2. The method for constructing a high-performance simplified perovskite solar cell as described in claim 1, characterized in that... In step 1), the conductive substrate is fluorine-doped tin oxide conductive glass.
3. The method for constructing a high-performance simplified perovskite solar cell as described in claim 1, characterized in that... In step 1), the ultrasonic cleaning time is 10-20 minutes; the ultraviolet-ozone cleaning time is 10-20 minutes.
4. The method for constructing a high-performance simplified perovskite solar cell as described in claim 1, characterized in that... In step 2), the alkali metal halide is selected from any one of LiF, NaF, KF, KCl, KBr, and KI.
5. The method for constructing a high-performance simplified perovskite solar cell as described in claim 1, characterized in that... In step 2), the concentration of the alkali metal halide aqueous solution is 1 to 4 mg / mL.
6. The method for constructing a high-performance simplified perovskite solar cell as described in claim 1, characterized in that... In step 2), the spin coating speed can be 1000-3000 rpm, and the spin coating time can be 10-30 s; the annealing can be performed at 100-150℃ for 10-30 min.
7. The method for constructing a high-performance simplified perovskite solar cell as described in claim 1, characterized in that... In step 3), the perovskite material is FACsMAPb(I 0.92 Br 0.08 3; The volume ratio of DMF to DMSO in the solvent is 1:
4.
8. The method for constructing a high-performance simplified perovskite solar cell as described in claim 1, characterized in that... In step 3), the perovskite light-absorbing layer is prepared by one-step spin coating. The film is spin coated in a glove box at a speed of 1000-4000 rpm for 10-30 s. Then, it is annealed at 100°C for 20-50 min. Ethyl acetate is used as the antisolvent.
9. The method for constructing a high-performance simplified perovskite solar cell as described in claim 1, characterized in that... In step 4), the concentration of the chlorobenzene solution of Spiro-OMeTAD is 60-80 mg / mL; the concentration of the acetonitrile solution of Li-TFSI is 520 mg / mL; and the thickness of Spiro-OMeTAD is 10-50 nm.
10. The method for constructing a high-performance simplified perovskite solar cell as described in claim 1, characterized in that... In step 5), the thickness of the electrode is 30–120 nm.
Citation Information
Patent Citations
Carbon-based perovskite solar cell based on multifunctional interface modification layer
CN110676385A
Organic-inorganic hybrid perovskite solar cell and preparation method thereof
CN111106247A